Juridical Analysis of the Use of Deed Under Hand as the Basis for Making PKR Deed in the Form of Authentic Deed by Notary in the Conception of Legal Certainty - SARI, Ni Made Arnita; KOSASIH, Johannes Ibrahim; AGUNG, Anak Agung Istri (Indonesia Strategic Sustainability, 2025)
Purpose:This study aims to juridically examine the suitability of using deeds under the hand as a legal basis in notarial practice and analyze the form of notary liability in the context of legal certainty.Methodology:The method used is normative legal research with statutory, conceptual, and case approaches. Data was collected through a literature study, interviews with five notaries, and analysis of three concrete cases, including case No. 616 K/PK/Pdt/2023.Findings: The results show that although the use of handwritten documents is still often encountered in practice, notaries are obliged to ensure the validity of the contents and identity of the parties before being stated in the authentic deed. Legal responsibility is attached to the notary both civilly, administratively, and criminally if there is an error or dispute due to the deed made. The unclear norms regarding the limits of the use of underhand documents show the need for legal clarity so that the deed made remains valid, strong, and does not cause legal loopholes.Implication Therefore, there is a need for legal reform to create clarity of norms regarding the limits of the use of underhand documents so that the deed made remains valid, strong, and does not cause legal gaps.